2006
DOI: 10.1007/s11145-006-9027-9
|View full text |Cite
|
Sign up to set email alerts
|

Name writing but not environmental print recognition is related to letter-sound knowledge and phonological awareness in pre-readers

Abstract: This paper reports a study exploring the associations between measures of two levels of phonological representation: recognition (epi-linguistic) and production (metalinguistic) tasks, and very early reading and writing skills. Thirty-eight pre-reading Ottawa-area children, aged 4-5 years, named environmental print (EP), wrote their own name, identified correct names and EP words amongst foils and detected foil letters within EP and names. Results showed that phonological awareness and letter-sound knowledge w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
35
3
9

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 30 publications
7
35
3
9
Order By: Relevance
“…by the exposure to books [e.g., [16,17]]. It has been proven to be a significant predictor of PA development [18,19,20,21]. Burgess and Lonigan [22] assessed PA and LK in 4- to 5-year-old preschool children.…”
Section: Introductionmentioning
confidence: 99%
“…by the exposure to books [e.g., [16,17]]. It has been proven to be a significant predictor of PA development [18,19,20,21]. Burgess and Lonigan [22] assessed PA and LK in 4- to 5-year-old preschool children.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between children's namewriting skill and other literacy skills was examined in previous studies (Justice et al, 2005;. A significant correlation was found between name-writing and phonological awareness by Blair and Savage (2006), between letter-knowledge (naming lower cases and upper cases, recognizing letters and letter sounds) and name-writing by Drouin and Harmon (2009) and between name-writing and recognizing meaningful and meaningless words by Haney et al (2003). Puranik et al (2011) found a relationship between name-writing skill and print-knowledge.…”
Section: Discussionmentioning
confidence: 98%
“…Previous researches mostly focused on the relationship of name-writing with other literacy skills such as phonological awareness, knowledge of letters and print awareness (Blair and Savage, 2006;Drouin and Harmon, 2009;Haney et al, 2003;Justice et al, 2005;Puranik et al, 2011;Welsh et al, 2003). For that reason, the present study analyzed the connection between name writing and writing readiness as two distinct aspects of writing development in preschool children.…”
Section: Significance Of the Studymentioning
confidence: 99%
“…The writing of one's own name may start as a logographic event; the name is one unit with no recognition of letter values. The ability to write one's name has been shown to correlate substantively with alphabet knowledge, print knowledge, letter sound knowledge and phonological awareness (Blair and Savage, 2006;Bloodgood, 1999;Puranik, Lonigan and Kim, 2011;Welsch, Sullivan and Justice, 2003). Bloodgood has a seven point scale whereas Puranik and Lonigan, 2012 score name writing on a nine point scale.…”
Section: Name Writing and Name Lengthmentioning
confidence: 99%